2003
DOI: 10.2337/diacare.26.3.668
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Screening for Diabetes in Michigan

Abstract: OBJECTIVE -To describe and evaluate a community-based diabetes screening program supported by the Michigan Department of Community Health.RESEARCH DESIGN AND METHODS -Between 1 June 1999 and 31 December 1999, community screening for diabetes was conducted by voluntary organizations using a standard protocol, American Diabetes Association (ADA) questionnaires, and ADA capillary plasma glucose criteria.RESULTS -A total of 3,506 individuals were screened, 14% of whom did not meet criteria for screening. Of the 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…4 Prior reports of diabetes screening in community and clinical venues have yielded mixed results, often limited by low prevalence rates and poor follow-up. [36][37][38] Similar to any disease screening, patient adherence with confirmatory testing and subsequent therapy is vital to the successful implementation. Additionally, the cost-effectiveness of opportunistic diabetes screening is unclear and will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Prior reports of diabetes screening in community and clinical venues have yielded mixed results, often limited by low prevalence rates and poor follow-up. [36][37][38] Similar to any disease screening, patient adherence with confirmatory testing and subsequent therapy is vital to the successful implementation. Additionally, the cost-effectiveness of opportunistic diabetes screening is unclear and will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the absolute costs associated with population screening are less, fewer people require population screening than opportunistic screening (18.2 million vs. 54.4 million). Studies of community screening have suggested that the yield of screening may be higher among those without regular health care (13). However, even if the yield is twofold higher in population-based screening, it remains less efficient.…”
Section: Cost Analysismentioning
confidence: 99%
“…Community screening outside a health care setting is not recommended because people with positive tests may not seek, or have access to, appropriate follow-up testing and care. Community testing may also be poorly targeted; i.e., it may fail to reach the groups most at risk and inappropriately test those at very low risk or even those who have already been diagnosed (38).…”
Section: Community Screeningmentioning
confidence: 99%